2013
DOI: 10.4172/2155-9880.s12-003
|View full text |Cite
|
Sign up to set email alerts
|

Troponin Testing in the Emergency Setting: How Good are we?

Abstract: Objectives: The purpose of this audit was to ascertain whether troponin tests are requested appropriately for acute admissions via A&E and EAU at the John Radcliffe Hospital, Oxford. Troponin tests are not 100% specific, and commencing the ACS protocol is not without risks. Inappropriate tests could result in minimally positive levels, and starting antiplatelets in these situations could lead to unnecessary complications.Methods: Data was collected on two 24-hour periods for all admissions to A&E and EAU (Emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…4 A study from a large teaching hospital in Oxford where 40% of the troponin tests were ordered inappropriately showed that in addition to patient harm and over utilization of hospital resources, the cost of inappropriate tests amounted to 320£ over a period of just 48 hours. 12 In our study, single troponin orders were used more extensively and inappropriately compared to serial orders. This is similar to what has been observed by Davey's 14 audit in 3 Australian hospitals where it was shown that majority of the single troponin orders were used more than the serial orders.…”
Section: Brief Communicationmentioning
confidence: 96%
See 2 more Smart Citations
“…4 A study from a large teaching hospital in Oxford where 40% of the troponin tests were ordered inappropriately showed that in addition to patient harm and over utilization of hospital resources, the cost of inappropriate tests amounted to 320£ over a period of just 48 hours. 12 In our study, single troponin orders were used more extensively and inappropriately compared to serial orders. This is similar to what has been observed by Davey's 14 audit in 3 Australian hospitals where it was shown that majority of the single troponin orders were used more than the serial orders.…”
Section: Brief Communicationmentioning
confidence: 96%
“…The serial troponin orders were further categorized as shown in troponin testing that revealed 23-46% of requested troponin tests to be inappropriate. 3,4,[12][13][14] In one such study, Abusalma et al 3 found that 41.8% of the Tn I tests were requested inappropriately. The study was followed up after some educational intervention which resulted in the reduction of inappropriate testing of troponin almost by half compared to earlier numbers.…”
Section: Brief Communicationmentioning
confidence: 99%
See 1 more Smart Citation